Does care at a cardiac arrest centre improve outcome after out-of-hospital cardiac arrest? — A systematic review. (April 2019) - Yeung, J.; Matsuyama, T.; Bray, J.; Reynolds, J.; Skrifvars, M.B.
Abstract: Aim: To perform a systematic review to answer 'In adults with attempted resuscitation after non-traumatic cardiac arrest does care at a specialised cardiac arrest centre (CAC) compared to care in a healthcare facility not designated as a specialised cardiac arrest centre improve patient outcomes?' Methods: The PRISMA guidelines were followed. We searched bibliographic databases (Embase, MEDLINE and the Cochrane Library (CENTRAL)) from inception to 1st August 2018. Randomised controlled trials (RCTs) and non-randomised studies were eligible for inclusion. Two reviewers independently scrutinized studies for relevance, extracted data and assessed quality of studies. Risk of bias of studies and quality of evidence were assessed using ROBINS-I tool and GRADEpro respectively. Primary outcomes were survival to 30 days with favourable neurological outcomes and survival to hospital discharge with favourable neurological outcomes. Secondary outcomes were survival to 30 days, survival to hospital discharge and return of spontaneous circulation (ROSC) post-hospital arrival for patients with ongoing resuscitation. This systematic review was registered in PROSPERO (CRD 42018093369) Results: We included data from 17 observational studies on out-of-hospital cardiac arrest (OHCA) patients in meta-analyses. Overall, the certainty of evidence was very low. Pooling data from only adjusted analyses, care at CAC was not associated with increased likelihood of survival to 30 days with favourable neurological outcome (OR 2.92, 95% CI 0.68–12.48) and survival to 30 days (OR 2.14, 95% CI 0.73–6.29) compared to care at other hospitals. Whereas patients cared for at CACs had improved survival to hospital discharge with favourable neurological outcomes (OR 2.22, 95% CI 1.74–2.84) and survival to hospital discharge (OR 1.85, 95% CI 1.46–2.34). Conclusions: Very low certainty of evidence suggests that post-cardiac arrest care at CACs is associated with improved outcomes at hospital discharge. There remains a need for high quality data to fully elucidate the impact of CACs.